2012
DOI: 10.1080/10911359.2012.647473
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Differences in Family Involvement and Depressive Symptoms across Latino Adolescent Groups

Abstract: This study investigated the association between family involvement and depressive symptoms among a sample of 187 Dominican, Mexican, and Central American adolescents from the Longitudinal Immigrant Student Adaptation Study. The study used the transactional stress model as its theoretical foundation. Findings from a multiple regression model suggest that low levels of family involvement were significantly related to higher levels of depressive symptoms for Dominican youths but not for Mexican or Central America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…Consistent with previous research (Céspedes & Huey, 2008; Dawson et al, 2012), the present study raises attention to the role of gender in depressive symptomatology. Although some recent studies (Sirin et al, 2013; Takeuchi et al, 2007) have suggested that gender differences in mental health symptomatology may vary by nativity status, the present study indicates that both U.S.-born and foreign-born girls report higher levels of depressive symptoms compared with boys.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with previous research (Céspedes & Huey, 2008; Dawson et al, 2012), the present study raises attention to the role of gender in depressive symptomatology. Although some recent studies (Sirin et al, 2013; Takeuchi et al, 2007) have suggested that gender differences in mental health symptomatology may vary by nativity status, the present study indicates that both U.S.-born and foreign-born girls report higher levels of depressive symptoms compared with boys.…”
Section: Discussionsupporting
confidence: 91%
“…Although some recent studies (Sirin et al, 2013; Takeuchi et al, 2007) have suggested that gender differences in mental health symptomatology may vary by nativity status, the present study indicates that both U.S.-born and foreign-born girls report higher levels of depressive symptoms compared with boys. It is possible that girls are more likely than boys to be socialized to internalize distress, and therefore are more likely to report symptoms of depression and other internalizing disorders (Dawson et al, 2012). Furthermore, gender-based socialization, the challenging task of negotiating mixed societal messages concerning gender, and the experience of rejection among girls who do not meet gender-based societal expectations have all been thought to contribute to higher levels of depressive symptomatology among girls when compared with boys (Barrett & White, 2002; Wisdom, Rees, Riley, & Weis, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theory and empirical evidence suggest that family influences are particularly central in the developmental and cultural ecologies of Latinx adolescents (e.g., Cupito, Stein, Gonzalez, & Supple, 2016). For example, many Latinx adolescents emphasize the role of the family through shared familism values ( familismo ; Sabogal, Marín, Otero-Sabogal, Marín, & Perez-Stable, 1987), sustain ties to cultural values via family connectedness (Dawson, Perez, & Suárez-Orozco, 2012), and routinely engage in family assistance behaviors (Telzer & Fuligni, 2009). As a guiding set of cultural values, familismo encourages family members to support one another (García-Coll & Vázquez García, 1995) and likely fosters environments that promote access to the benefits of social support (Corona et al, 2017, p. 549; Stein, Gonzalez, Cupito, Kiang, & Supple, 2015).…”
Section: Role Of Perceived Social Support From Family and Peersmentioning
confidence: 99%